Stumps of Eucalyptus globulus as a source of antioxidant and antimicrobial polyphenols - Luís, Ângelo (2017)
These past years have seen an enormous development of the area of natural antioxidants and antimicrobials. Eucalyptus globulus is widely cultivated in subtropical and Mediterranean regions in intensive short rotation coppice plantations. In the Portuguese context, E. globulus is the third species in terms of forest area. The stump is the basal part of the tree, including the near-the-ground stem portion and the woody roots that remain after stem felling. The purpose of this work was to study the phytochemical profile and to evaluate the antioxidant and antimicrobial properties of several crude stump wood and stump bark extracts of E. globulus, comparing it with similar extracts of E. globulus wood (industrial chips). The results showed the presence of high concentrations of total phenolic compounds (>200 mg GAE/g extract) and flavonoids (>10 mg QE/g extract) in E. globulus stump extracts. Generally the stump wood extracts stands out from the other ones, presenting the highest percentages of inhibition of linoleic acid oxidation. It was also possible to conclude that the extracts were more active against Gram-positive bacteria, presenting low MIC values. This study thus provides information supporting the economic valorization of E. globulus stump wood